Local Community Responses to the Commodification of Livelihoods in Tourism Destination of Borobudur - Janianton Damanik; Mohamad Baiquni; Hermawan Yusuf; Petrus Jilbert Millians Pulla (Jurnal Ilmu Sosial dan Humaniora, 2024)
The commodification of local community livelihoods occurs in many tourism destinations. How community responds to this does not seem to have been discussed much in previous researches. This paper aims to explore the response of local communities to the increasing practice of commodifying livelihoods in the super priority destination Borobudur based on their three socio-economic variables, namely: social position, education and the volume of assets owned. A survey method has been chosen to collect main data which is analysed using inferential statistics. It was found that the commodification of livelihood assets occurred intensively due to the development of tourism in these destinations. It has been proven that the commodification of livelihoods has been responded differently by local communities. The differences in responses are clearly shown by socio-economic background. Those with higher education are more responsive in the sense of agreeing with commodification compared to those with low education. Apart from that, the social position also influences different responses to the commodification of livelihoods in the tourism destination. Likewise, the volume of assets owned also differentiates their response to the commodification of livelihoods. From these findings it was concluded that the response to the commodification of livelihoods related to the development of tourism destinations was responded differently by local communities. The implication is that destination development needs to pay attention to preserving the livelihoods of local communities as one of the strengths of attraction.